Analisis Pengelolaan Pajak Parkir Dan Retribusi Parkir Pada Pendapatan Asli Daerah Kota Pekanbaru - rahmat fajri, zahaldi; Fionasari, Dwi; Hetri Suriyanti, Linda (P3M Politeknik Negeri Bengkalis, 2024)
This research aims to evaluate the effectiveness and contribution of parking tax and parking fees as sources of Local Revenue (Pendapatan Asli Daerah) in Pekanbaru City. The type of research is qualitative. The method used is a descriptive qualitative approach, with an analysis of growth and effectiveness assess the extent to which these two types of revenue play a role. The variable of this research is parking tax, parking fees, and local revenue. The sample of this research is a head and staff of regional original revenue agency and department of transportation. This research use qualitative method. Based on data collected through growth calculations, effectiveness assessments, and interviews, it was found that parking tax and parking fees are currently very effective as sources of Local Revenue. However, both types of revenue show significant potential to increase their contribution to the Local Revenue of Pekanbaru City.